RH knowledge and service utilization among unmarried rural-to-urban migrants in three major cities, China - Li Zi; Dib Hassan H; Zhu Minmin; Liu Zhiyong; Shi Shuhua; Wang Zengzhen (BMC, 2011)
Abstract Background Large numbers of unmarried migrants are on the continuous move from rural-to-urban areas within China mainland, meanwhile their Reproductive Health (RH) is underserved when it is compared with the present urban RH policies. The purpose of this study is to investigate the RH knowledge and the utilization of RH services among unmarried migrants. Methods A cross-section survey was performed in three cities in China-Shenzhen, Guangzhou and Wuhan. A total of 3,450 rural-to-urban unmarried migrants were chosen according to a purposive sampling method. Around 3,412 (male: 1,680, female: 1,732) were qualified for this study. A face-to-face structured questionnaire survey was used, which focused on the knowledge concerning "fertility, contraception and STD/AIDS," as well as RH service utilization. Results Among unmarried migrants the RH knowledge about pregnancy-fertilization (29.4%) and contraception (9.1%) was at its lowest level. Around 21% of unmarried migrants had pre-marital sexual experience and almost half (47.4%) never used condoms during sexual intercourse. The most obtained RH services was about STD/AIDS health education (female: 49.6%, male: 50.2%) and free prophylactic use of contraceptives and/or condoms (female: 42.5%, male: 48.3%). As for accessing RH checkup services it was at its lowest level among females (16.1%). Those who migrated to Shenzhen (OR = 0.64) and Guangzhou (OR = 0.53) obtained few RH consultations compared to those in Wuhan. The white collar workers received more RH consultations and checkup services than the blue collar workers (all group P < 0.01). Conclusion RH knowledge and the utilization of RH services amongst unmarried migrants remain insufficient in the three studied major cities. This study reveals the important gaps in the RH services' delivery, and highlights the requirements for tailored interventions, including further research, to address more effectively the demands and the needs of the unmarried migrant populations.